A study on the attitudes toward health care and curative practices of people in an urban area - (:unkn) unknown (My University, 1998)
Çalışma Kocaeli il merkezinde Ekim-Kasım 1991 'de ke-sitsel olarak yürütüldü. Rastgele seçilmiş ev halkı üyelerinin (n=812) erken tanı ve tedavi edici işlemler hakkındaki eğilim-leri ev ziyaretleri ile ve aynı bölgedeki 6 eczahaneye başvuru (n=1331 başvuru) sebepleri kaydedildi. Çalışma grubunun çoğunluğu düzenli kontrolün anlamını ve önemini bilmesine rağmen o ana kadar ancak %7'si bu amaçla hekime başvur-muştu. Özellikle ağrılı durumlar için kendi kendini tedavi etme baskın yardım arama durumu olarak bulundu. Reçete edilmeyen ilaçların reçete edilenlere oranı 1/1.75 olarak tespit edildi. Analjezikler, antipiretikleı; ekspektomnlar ve antitussif-ler en sık reçetesiz olarak istenen ilaçlar olarak tespit edildi.

This cross-sectional study was carried during October-November J991 in city center of Kocaeli province, western Turkey. Attitudes of randomly selected households (n=812) to-ward secondary prevention and curative practices were searched during house visits and reasons for attendence to the 6 pharmacies (n = !33I attendances) in the same region was recorded. Majority of the study group knew the meaning and importance of regular check-ups while only 7% had ever expe-rienced. Self medication was found to be the dominant mode of help-seeking behaviour especially for painful conditions. The proportion of unprescribed drugs to the prescribed was 1/1.75 and analgesics, antipyretics, expectorants and antitussives were the most commonly requested unprescribed drugs.
Şehirde yaşayan kişilerin sağlığın korunması ve tedavi işlemleri hakkındaki eğilimleri üzerine bir araştırma
Keywords: Genel ve Dahili Tıp